A compact broadband ESD protection circuit using multi‐layer helical inductor. Issue 20 (22nd June 2021) - Zou, Wang‐Hui; Tang, Peng; Zhu, Zhi‐Hua
Abstract: Here, a broadband electrostatic discharge (ESD) protection circuit using area‐efficient multi‐layer helical inductors is presented. The proposed concept was verified in a 0.18 μm 1P6M CMOS process, and the circuit area is only 54 × 63 μm 2 . The measurement results show that a bandwidth of around 30 GHz is achieved, and the impedance matching is kept under –20 dB up to 40 GHz. The measured TLP and VF‐TLP currents reach 2.19 and 5.80 A, respectively, which indicates a good ESD robustness.